Efficiency improvement possibilities based on wool processing - Ergashev Gayrat Urolovich (THE INNOVATION ECONOMY, 2026)
Expansion of the raw material base for textile products from wool fiber based on the improvement of the initial processing technology of local coarse and semi-coarse wool fibers due to the expansion of the number of wool fiber processing and product production enterprises.